Guided Inquiry Learning: How to Improve Students' Argumentation Abilities in Science Learning? - Della Novri Yanti; Jaslin Ikhsan; Antuni Wiyarsi (Universitas Pendidikan Ganesha, 2023)
A big challenge for educators in carrying out learning that has undergone drastic changes. During the pandemic, learning activities carried out online were again carried out offline. This learning adaptation has a considerable impact on learning outcomes. Students have difficulty understanding chemical concepts and are passive in giving opinions in learning so it is difficult to integrate knowledge. During online learning activities, student learning resources are still focused on abstract concepts and books provided. The purpose of this study was to improve students' argumentation skills on chemistry in interpreting the knowledge obtained with the guided inquiry learning model. This type of research is a descriptive research with a quantitative approach. Data collection techniques used observation, argumentation ability tests, and documentation. The data obtained were analyzed using quantitative analysis techniques. Based on the results of the study, it showed that students were able to make claims but had difficulty presenting data and proving evidence. Students' initial argumentation abilities can be a reference for educators to determine future learning activities, with the hope that learning is designed not only to focus on achieving conceptual understanding but to develop students' argumentation abilities.